Association between body mass index and individual characteristics and the school context: a multilevel study with Portuguese children - Rafael S. Henrique; Thayse N. Gomes; Go Tani; José A.R. Maia (Jornal de Pediatria, 2018)
Objective: The aim of this study was to examine the association between individual and school context characteristics with the body mass index of Portuguese children. Methods: The sample comprised 1641 children (847 boys) aged 6–10 years from the North and Central regions of Portugal. Regarding the individual characteristics, age, gender, city of residence, levels of physical activity, and physical fitness were assessed. Concerning the school context characteristics, the surrounding environment, school size, presence of recreational characteristics and space, and presence of a sports court and of physical education classes were considered. Children's body mass index was the dependent variable. The multilevel analysis was carried out in HLM 7.0 software. Results: The predictors of the child and the school context explained, respectively, 97.3% and 2.7% of the total body mass index variance. Regarding the individual characteristics, older children, boys, and those who had lower performance at the 1-mile run/walk, curl-up, push-up, and higher performance in trunk lift tests showed higher BMI. Further, urban schools with higher recreational spaces were positively associated with children's body mass index. Conclusion: School context variables have a reduced effect on body mass index variation compared to the children's biological and behavioral characteristics. The authors therefore encourage strategies that aim to increasing children's physical fitness levels to help prevent excess weight. Resumo: Objetivo: Examinar a associação de características individuais e do contexto escolar no índice de massa corporal de crianças portuguesas. Método: A amostra compreendeu 1641 crianças (847 meninos) de 6 a 10 anos de idade. Em relação às características individuais foram utilizadas informações relativas ao sexo, à idade, à residência, à atividade física e à aptidão física. Em termos de contexto escolar, foram considerados o meio ambiente, o tamanho da escola, a presença de recreio, as características e dimensões do espaço disponível para o recreio, a existência de quadra poliesportiva e de aulas de Educação Física. O índice de massa corporal [kg/(m2)] foi a variável dependente. A análise multinível foi efetuada no software HLM 7.0. Resultados: Os preditores da criança e do contexto escolar explicaram, respectivamente, 97,3% e 2,7% da variância total do índice de massa corporal. Quanto às características individuais, a idade (mais velhos) e o sexo (meninos), bem como o desempenho reduzido nas provas de corrida/marcha da milha, do curl-up, do push-up e valores elevados no trunk lift estiveram associados ao aumento no índice de massa corporal. Escolas do meio urbano e escolas com maiores espaços para o recreio também estiveram positivamente associadas ao aumento do índice de massa corporal. Conclusões: As variáveis do contexto escolar têm um efeito reduzido na variação do índice de massa corporal comparativamente às características biológicas e comportamentais das crianças. Sugere-se a aplicação de programas visando o incremento dos níveis de aptidão física das crianças para prevenir o excesso de peso na infância. Keywords: Body mass index, Child, Schools, Environmental design, Multilevel analysis, Palavras-chave: Índice de massa corporal, Criança, Escolas, Planejamento ambiental, Análise multinível